Evaluation of Road Pavement Cracks in Malaysia - Bughrara, Neral F. A. (2008)

(untitled)
Road surface condition is one of the most important characteristics because it affects ride quality, operation cost, and vehicle dynamic load. Thus it is necessary to study all factors affect the roads conditions, and to evaluate the different types of pavement distresses occur in the Malaysian roads. For this reason, this research was conducted to evaluate the main problem that occur in the Malaysian roads, and to find out the reasons of such a pavement behavior. In order to do four federal highways profile were studied, and data was collected using four different techniques, and analyzed to specify the dominate pavement distresses occur in the Malaysian roads.